Entrepreneurship centres : global perspectives on their contributions to higher education institutions - Maas, G. 1959-; Jones, Paul, 1967 September 22- (Palgrave Macmillan, 2017)
Focusing on the role entrepreneurship centres can play within the UK and other countries; this edited volume explores the effective construction of viable and sustainable entrepreneurship centres. It questions how these Higher Education Centres contribute to enterprise and entrepreneurship curriculum enhancement, research, and support to entrepreneurs. Entrepreneurship Centres responds to the renewed focus on Higher Education Institutions to play a meaningful role in socio-economic development and the need for such centres to act as an equal component to the traditional roles of teaching and research within Universities. With case studies from the UK, Africa, Europe, and Canada, this collection contributes to the debate on whether entrepreneurship centres can and should play an important role in entrepreneurship activities within HEIs. Gideon Maas is Director of the International Centre for Transformational Entrepreneurship at Coventry University, UK. Previously the Director of Futures Entrepreneurship Centre at Plymouth University, he has created entrepreneurship centres at various universities during his career. Paul Jones is Deputy Director of the International Centre for Transformational Entrepreneurship and Professor of Entrepreneurship at Coventry University, UK. Paul is Editor-in-Chief of the Journal of Entrepreneurial Behaviour and Research and Associate Editor for the International Journal of Management Education. He has published widely including one edited book, 48 journals and over 100 conference papers.
Keywords: Entrepreneurship.; Entrepreneurship -- Study and teaching (Secondary); Business and education.; Education, Higher.; elektronické knihy; electronic books